A case of rheumatoid arthritis with multiple lung rheumatoid nodules successfully treated with tofacitinib. (2nd January 2021) - Kondo, Masahiro; Murakawa, Yohko; Honda, Manabu; Yanagawa, Takashi; Nagasaki, Makoto; Moriyama, Mayuko; Watanabe, Yohei; Kakimaru, Hiroyuki
Abstract: Sporadic cases of rheumatoid nodules (RNs) in the lung during treatment with tumour necrosis factor (TNF) inhibitors have been reported, but no treatment has been established. Here, we report a case of symptomatic lung RNs refractory to abatacept (ABT) and intravenous cyclophosphamide (IVCY) that improved with tofacitinib (TOF) treatment. A 75-year-old Japanese woman with a 10-year history of rheumatoid arthritis (RA) presented with a cough and haemoptysis during treatment with etanercept (ETN). Radiographic examinations revealed multiple nodules that were diagnosed as lung RNs via biopsy. The ETN was discontinued and ABT followed by IVCY was introduced; however, neither was sufficiently effective against the lung RNs. Thereafter, TOF was started and the lung RNs improved rapidly. The precise mechanisms that induce RNs during treatment with TNF inhibitors are unknown. Cytokines (IL-23 and IL-6) are suspected to be involved. TOF may be a reasonable strategy for treating symptomatic lung RNs.